Karakteristik Sensori, Kimia, dan Aktivitas Antioksidan Kue Egg Roll dengan Penambahan Tepung Temulawak (Curcuma xanthorrhiza Roxb) - Refani Fadli Rahman; Aminullah; Distya Riski Hapsari (Universitas Djuanda, 2023)
Javanese turmeric is one of the Indonesian herbs that is underutilised because of its pungent aroma and bitter taste. This study aims to investigate the effect of the ratio of wheat flour to Javanese turmeric powder on the sensory characteristics, chemical properties and antioxidant activity of egg roll cakes. The research method used was a Completely Randomized Design (CRD) with four levels of treatment, namely the ratio of wheat flour to Javanese turmeric powder of 28:2, 26:4, 24:6 and 22:8. The addition of Javanese turmeric powder can increase the moisture content, curcumin content and antioxidant activity of egg roll cake, but reduce the sensory acceptability of the product. During the production process of the egg roll cake, the curcumin content decreased by 4.79% - 6.50%. The best treatment for egg roll cake based on the de Garmo method is the addition of 2% Javanese turmeric powder that has a moisture content of 3.91%, curcumin content of 0.00311 g/g (0.31%) and antioxidant activity of 5.04%.